Determinação de bispiribaque-sódico, quincloraque e tebuconazole em água de lavoura de arroz irrigado empregando SPE e HLPC-DAD - Vicari, Michele Camara de (2009)
Rice is one of the most produced and consumed cereal in the world. It plays a strategic role both economically and socially. Southern is responsible for about 60% of Brazilian rice production, which is directly linked to the intensive use of pesticides. Considering it, the study of the remaining of such compounds in crops to assess the risks of environmental contamination is socio-economically very important. Based on that this paper, an analytical approach has been developed and validated in order to determine the residues of bispyribac-sodium, quinclorac, and tebuconazole in water from irrigated rice crops, using Solid Phase Extraction (SPE) and High Performance Liquid Chromatography with Diode Array Detection (HPLC-DAD). The approach consists of preconcentration of water samples in SPE cartridges with 500 mg of C18, followed by elution with methanol and pesticides determination through HPLC-DAD. In the validation of the method, the analytical curve and linearity, limit of detection (LOD), limit of quantification (LOQ), precision (repetitivity and intermediate precision), as well accuracy (recovery) were assessed. The analytical curves displayed linearity between 0.03 and 10 mg L-1 for quinclorac, 0,1 e 10 mg L-1 for bispyribac-sodium and between 0,05 e 10 mg L-1 for tebuconazole, with determination coefficients higher than 0.9999. LOQ values for the approach, considering preconcentration phase of 250 times, were of 1.2 μg L-1 for bispyribac-sodium, 0.4 μg L-1 for quinclorac, and 0.6 μg L-1 for tebuconazole. The method presented recovery values between 76.1 and 116.5% and RSD values smaller than 19.8%. All the validation parameters are within the suggested limits for validation of chromatographic methods. The validated method was applied in the study of pesticides dissipation in water from irrigated rice crops. Bispyribac-sodium and quinclorac were found up to 28 and 91 days after the compounds have been used, respectively and tebuconazole to 21 days after the compound have been used.